Managed Futures for Institutional Investors : Analysis and Portfolio Construction. (Bloomberg financial series., 2011)
A practical guide to institutional investing success Managed Futures for Institutional Investors is an essential guide that walks you through the important questions that need to be addressed before investing in this asset class and contains helpful direction for investors during the investing process. Backed by years of institutional experience, the authors reveal the opportunities offered by managed futures. They also include information on practices in the managed futures area and present the various analytical tools and building blocks required to use managed futures effe.